2020
DOI: 10.1007/s13762-020-02858-y
|View full text |Cite
|
Sign up to set email alerts
|

A statistical study for impacts of environmental conditions on the rapid spread of new corona virus

Abstract: The new coronavirus, COVID-19, spread quickly and causes the death for thousands of people, and a major freeze for the economy and people activities worldwide. This study made statistical analysis for the influences of the environmental conditions such as temperature, humidity, precipitation, wind, and air pollution, which may aid in spreading this virus very fast. The study also investigated statistically the impact of people customs such as smoking, drinking wine, and eating pig meat on the number of deaths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
3
7
0
Order By: Relevance
“…Wind speed could affect directly or indirectly to reduce the infection transmission, which might due to social behaviour as high wind speed makes people stay more in home, so less social interaction happens, or the wind speed spreads the suspended particles in the atmosphere, which it might have a significant role in the transmissions particularly in the capitals. This finding is in line with the results of the study (Ahmed and Ghanem 2020 ). However, our findings show that the precipitation does not have a significant effect on the COVID-19 infected cases, which is in the same trend with finding of the study (Ahmed and Ghanem 2020 ).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Wind speed could affect directly or indirectly to reduce the infection transmission, which might due to social behaviour as high wind speed makes people stay more in home, so less social interaction happens, or the wind speed spreads the suspended particles in the atmosphere, which it might have a significant role in the transmissions particularly in the capitals. This finding is in line with the results of the study (Ahmed and Ghanem 2020 ). However, our findings show that the precipitation does not have a significant effect on the COVID-19 infected cases, which is in the same trend with finding of the study (Ahmed and Ghanem 2020 ).…”
Section: Resultssupporting
confidence: 93%
“…This finding is in line with the results of the study (Ahmed and Ghanem 2020 ). However, our findings show that the precipitation does not have a significant effect on the COVID-19 infected cases, which is in the same trend with finding of the study (Ahmed and Ghanem 2020 ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The occurrence and spread of COVID-19 are closely related to environmental issues such as air pollution and water pollution. A survey of global environmental conditions found that environmental conditions with suitable temperature, high air humidity and rainfall, and high air pollution are more conducive to the spread of COVID-19 (Ahmed and Ghanem 2020 ). And the COVID-19 virus can survive for many days in untreated sewage.…”
Section: Introductionmentioning
confidence: 99%